PENERAPAN STRATEGI PEMBELAJARAN TOPICAL REVIEW DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMP YP PGRI 4 MAKASSAR - Eka Adnan Agung (Cross-border, 2021)
This research is to research a class action whose aim is to increase the activity and learning outcomes ips topical learning through a strategy review class students VIII YP PGRI 4 Makassar. Junior High School Research is done to get the necessary data-data through observation and the provision of testing as. data sourcesThe results of research on the cycle 1 showed that activity and student learning outcomes IPS class VIII has not been for students who received scores of & gt; 75 just 13 people or 43,3 % who rose to on the standard exhaustiveness and are not complete 17 people or 56,7 % while in the cycle II shows that there have been increased activity and learning outcomes students which 29 students who achieve exhaustiveness or 96,7 % and who do not reach upon default exhaustiveness just one people or 3,3. The activity of students in learning ips has increased in aspect listening explanation, teacher ask questions and responses, answer the question, noted a task assigned by the teacher, active in a discussion group increased namely average 1 66,33 cycle and cycles II 78. Students study results obtained from the cycle to the cycle is the first two 66,33 and 78.